Species composition and size distribution of the tropical estuarine fishes in Matang Mangrove Forest Reserve (MMFR), Malaysia - MUHAMAD IKRAM ZURAINI; SITI TAFZILMERIAM SHEIKH ABDUL KADIR; MUHAMMAD FADHLI MAT SOBRI; AZMI MARZUKI MUDA; SITI WAZNAH ABDURAHMAN; NURZUHRAH HASSAN; SAIFULLAH ARIFIN JAAMAN; MAIZAH M. ABDULLAH (Biodiversitas Journal of Biological Diversity, 2026)
Abstract. Zuraini MI, Kadir STSA, Sobri MFM, Muda AM, Abdurahman SW, Hassan N, Jaaman SA, Abdullah MM. 2026. Species composition and size distribution of the tropical estuarine fishes in Matang Mangrove Forest Reserve (MMFR), Malaysia. Biodiversitas 27 (1): d270137. https://doi.org/10.13057/biodiv/d270137. The Matang Mangrove Forest Reserve (MMFR) in Perak, Malaysia, represents one of the most well-managed and ecologically significant mangrove ecosystems in the world. Spanning over 40,000 ha and protected since 1906, MMFR provides critical nursery and feeding habitats for a wide range of marine fauna, including commercially important fish, crustaceans, shellfish, and endangered marine cetaceans. This study was conducted to determine the diversity, composition and size distribution of estuarine fishes in three estuaries connected to the MMFR namely Kuala Larut (KL), Kuala Sangga (KS) and Kuala Gula (KG). Samplings were conducted in October, November and December 2021 using gill nets that were deployed along the estuarine gradients at the upper (near riverine areas), the middle, and the mouth (near the coastal interface) estuary. A total of 2,756 fish individuals, representing 42 species across 21 families, were collected. The most abundant family was Engraulidae (N: 1,400), dominated by Thryssa kammalensis by 49.96%, followed by the family Mugilidae (N: 504), primarily composed of Paramugil parmatus by 14.77%, and Ariidae (N: 457), dominated by Arius maculatus by 10.19%. The Shannon diversity index (H′) was highest at KL (2.12), followed by KS (1.63) and KG (1.35), with Pielou’s evenness index (J′) mirrored this trend. Meanwhile, species richness is highest at KS, followed by KL and KG, indicating heterogeneity in community composition among estuaries. The presence of three Near Threatened (NT) species listed by the IUCN, namely Protonibea diacanthus, Brevitrygon walga and Arius gagora, underscores the ecological significance of the estuarine habitats within the MMFR. This study provides an updated baseline data on fish diversity in MMFR, offering critical insights to guide future conservation planning and sustainable resource management.